Human Suprapatellar Fat Pad-Derived Mesenchymal Stem Cells Induce Chondrogenesis and Cartilage Repair in a Model of Severe Osteoarthritis - Ignacio Muñoz-Criado; Jose Meseguer-Ripolles; Maravillas Mellado-López; Ana Alastrue-Agudo; Richard J Griffeth; Jerónimo Forteza-Vila; Ramón Cugat; Montserrat García; Victoria Moreno-Manzano (Stem Cells International)
Cartilage degeneration is associated with degenerative bone and joint processes in severe osteoarthritis (OA). Spontaneous cartilage regeneration is extremely limited. Often the treatment consists of a partial or complete joint implant. Adipose-derived stem cell (ASC) transplantation has been shown to restore degenerated cartilage; however, regenerative differences of ASC would depend on the source of adipose tissue. The infra- and suprapatellar fat pads surrounding the knee offer a potential autologous source of ASC for patients after complete joint substitution. When infrapatellar- and suprapatellar-derived stromal vascular fractions (SVF) were compared, a significantly higher CD105 (+) population was found in the suprapatellar fat. In addition, the suprapatellar SVF exhibited increased numbers of colony formation units and a higher population doubling in culture compared to the infrapatellar fraction. Both the suprapatellar- and infrapatellar-derived ASC were differentiated in vitro into mature adipocytes, osteocytes, and chondrocytes. However, the suprapatellar-derived ASC showed higher osteogenic and chondrogenic efficiency. Suprapatellar-derived ASC transplantation in a severe OA mouse model significantly diminished the OA-associated knee inflammation and cartilage degenerative grade, significantly increasing the production of glycosaminoglycan and inducing endogenous chondrogenesis in comparison with the control group. Overall, suprapatellar-derived ASC offer a potential autologous regenerative treatment for patients with multiple degenerative OA.